Fabrication and evaluation of polymer-based esophageal stents for benign esophagus stricture insertion. Issue 20 (10th February 2016) - Yuan, Tianwen; Zheng, Reila; Yu, Jia; Edmonds, Laura; Wu, Wei; Cao, Jun; Gao, Fei; Zhu, Yueqi; Cheng, Yingsheng; Cui, Wenguo
Abstract : In benign esophageal strictures, polymeric lines and membranes were chosen to knit an esophageal stent for relieving esophageal lesions caused by esophageal stenosis and obstruction. Abstract : In benign esophageal strictures, an esophageal stent implantation can relieve esophageal lesions caused by esophageal stenosis and obstruction. However, the removal of metallic stents is difficult and biodegradable polymer stents show poor mechanical properties. In this study, polypropylene (PP) lines as skeleton fibers and silicone coating membranes were chosen to knit an esophageal stent for improved structural strength and easy removal. Mechanical testing demonstrated that the stent maintained its original mechanical characteristics after two hundred repeated compressions and pulls. According to a finite element simulation analysis of the stent, the left and right sides had higher stress concentrations than the loading contact site and the restraint site of both ends. The proliferation of smooth muscle cells showed no signs of cell toxicity. During an in vivo evaluation, the changes to the esophageal wall were significant: thinner epithelial and smooth muscle actin layers in the PP–silicone stent group than in the control group ( P < 0.05). Esophageal injury and collagen deposition following the stent insertion were similar to those of the control group ( P > 0.05). The esophageal PP–silicone stent insertion was feasible and provided reliable support for at least 4 weeks, with acceptable migration rates and without causing severe injury or collagen deposition. Therefore PP stents have great potential to provide a new method and practical basis for the treatment of benign esophageal strictures.